2022
DOI: 10.1007/s00203-022-03074-7
|View full text |Cite
|
Sign up to set email alerts
|

Community structure and co-occurrence network analysis of bacteria and fungi in wheat fields vs fruit orchards

Abstract: Soil microorganisms play a vital role in biogeochemical processes and nutrient turnover in agricultural ecosystems. However, the information on how the structure and co-occurrence patterns of microbial communities respond to the change of planting methods is still limited. In this study, a total of 34 soil samples were collected from 17 different elds of two planting types (wheat and orchards) along the Taige Canal in Yangtze River Delta. The distribution and diversity of bacterial and fungal communities in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 56 publications
2
8
1
Order By: Relevance
“…In the cultivated land of a karst area, Actinobacteria, Proteobacteria, Chloroflexi, and Acidobacteria were the dominant bacterial phyla (Figure 2c), and Ascomycota, Mortierellomycota, and Basidiomycota were the dominant fungal phyla (Figure 2d). Our findings are similar to those of several studies (Chen et al, 2020; Cui et al, 2022; Eo & Park, 2016). We found that the relative abundance of Ascomycota and Actinobacteria showed the following trend: uncultivated > cabbage > cocozelle > maize soils (Figure 2d and Table S7).…”
Section: Discussionsupporting
confidence: 93%
“…In the cultivated land of a karst area, Actinobacteria, Proteobacteria, Chloroflexi, and Acidobacteria were the dominant bacterial phyla (Figure 2c), and Ascomycota, Mortierellomycota, and Basidiomycota were the dominant fungal phyla (Figure 2d). Our findings are similar to those of several studies (Chen et al, 2020; Cui et al, 2022; Eo & Park, 2016). We found that the relative abundance of Ascomycota and Actinobacteria showed the following trend: uncultivated > cabbage > cocozelle > maize soils (Figure 2d and Table S7).…”
Section: Discussionsupporting
confidence: 93%
“…A diverse microbial community contributes to creating favorable growing conditions and enhancing crop productivity [ 56 ]. Consistent with previous studies [ 57 ], our research identified Proteobacteria , Acidobacteriota , Actinobacteriota , and Chloroflexi as the predominant bacterial phyla in the soils of cabbage, kale, cucumber, and tomato (Fig. 2 A and Table S5).…”
Section: Discussionsupporting
confidence: 92%
“…Changes in the composition of the bacterial community may lead to variations in the metabolic capacity, bio-degradation, and disease-suppression abilities. Previous studies have shown that the compositions of bacteria and fungi in the rhizospheres of many plants, such as Arabidopsis [30], sugarcane [31,32], wheat [33,34], sugar beet [35,36], and soybean [37][38][39], can vary with the plant's developmental stage. In actual production, the developmental stages of plants can generally be divided into four periods: seedling, development, flowering, and fruiting.…”
Section: Discussionmentioning
confidence: 99%